Effect of fluid loading with normal saline and 6% hydroxyethyl starch on stroke volume variability and left ventricular volume - Kanda, Hirotsugu (Int J Gen Med, 2015)
PURPOSE: The aim of this clinical trial was to investigate changes in stroke volume variability (SVV) and left ventricular end-diastolic volume (LVEDV) after a fluid bolus of crystalloid or colloid using real-time three-dimensional transesophageal echocardiography (3D-TEE) and the Vigileo-FloTrac™ system. MATERIALS AND METHODS: After obtaining Institutional Review Board approval, and informed consent from the research participants, 22 patients undergoing scheduled peripheral vascular bypass surgery were enrolled in the study. The patients were randomly assigned to receive 500 mL of hydroxyethyl starch (HES; HES group, n=11) or normal saline (Saline group, n=11) for fluid replacement therapy. SVV was measured using the Vigileo-FloTrac system. LVEDV, stroke volume, and cardiac output were measured by 3D-TEE. The measurements were performed over 30 minutes before and after the fluid bolus in both groups. RESULTS: SVV significantly decreased after fluid bolus in both groups (HES group, 14.7%±2.6% to 6.9%±2.7%, P<0.001; Saline group, 14.3%±3.9% to 8.8%±3.1%, P<0.001). LVEDV significantly increased after fluid loading in the HES group (87.1±24.0 mL to 99.9±27.2 mL, P<0.001), whereas no significant change was detected in the Saline group (88.8±17.3 mL to 91.4±17.6 mL, P>0.05). Stroke volume significantly increased after infusion in the HES group (50.6±12.5 mL to 61.6±19.1 mL, P<0.01) but not in the Saline group (51.6±13.4 mL to 54.1±12.8 mL, P>0.05). Cardiac output measured by 3D-TEE significantly increased in the HES group (3.5±1.1 L/min to 3.9±1.3 L/min, P<0.05), whereas no significant change was seen in the Saline group (3.4±1.1 L/min to 3.3±1.0 L/min, P>0.05). CONCLUSION: Administration of colloid and crystalloid induced similar responses in SVV. A higher plasma-expanding effect of HES compared to normal saline was demonstrated by the significant increase in LVEDV.